From Chalk-Dusters to Code: Economic Perspectives on Ai-Driven Education in Nepal - Dhakal, Gagan Sharma (Nepalese Journal of Economic Studies, 2025)
This study examined how artificial intelligence is being incorporated into Nepal’s education system, a nation renowned for its digital innovation. Through case study and document analysis methods, it assessed the practical effects, economic outcomes, and strategic challenges of AI adoption. This research identified AI’s potential for economic efficiency within education, while emphasizing the importance of fostering AI literacy among students and educators. Key concerns such as ethics and data privacy are explored, along with institutional strategies to address them. The paper concludes by highlighting AI’s transformative role in education and the necessity of strong policy and ethical foundations to guide responsible implementation and economic sustainability.